Diurnal behavior of dairy cows on alfalfa pastures supplemented with corn silage and concentrate - Peres Netto, D. (2014)
The diurnal ingestive behavior of dairy cows on alfalfa pastures supplemented with corn silage and concentrate was evaluated. Sixteen Holstein dairy cows in mid-lactation were used in a randomized block design. The treatments were partial replacement of corn silage for limited alfalfa grazing time (LGT) or unlimited grazing time (UGT). Rotational alfalfa grazing was used and the amount of concentrate fed was the same in both treatments. Behavioral activities observed were time spent grazing, rumination and idleness, during four days, from 8:00 AM to 7:00 PM. From 2:00 to 5:00 PM grazing was intermittent and short-lasting on UGT, whereas on LGT grazing activity was longer than UGT in the morning and at the end of the afternoon. Restriction in available grazing time clearly influenced the distribution of time spent with grazing, rumination and idleness throughout the day. However, this effect was not observed in the total time spent in these activities.